2008
DOI: 10.1130/gsat01803a.1
|View full text |Cite
|
Sign up to set email alerts
|

The mystery of the pre–Grand Canyon Colorado River—Results from the Muddy Creek Formation

Abstract: The Colorado River's integration off the Colorado Plateau remains a classic mystery in geology, despite its pivotal role in the cutting of Grand Canyon and the region's landscape evolution. The upper paleodrainage apparently reached the southern plateau in the Miocene, and recent work supports the longstanding idea that the river was superimposed over the Kaibab uplift by this time. Once off the plateau, the lower river integrated to the Gulf of California by downstream basin spillover from ca. 6-5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 30 publications
3
43
1
Order By: Relevance
“…4), this implies that a Miocene ancestral Colorado River never followed a westward route from the Glen Canyon area. This deduction agrees with the work of Pederson (2001), who found no evidence for an ancestral Colorado River having flowed west into the Muddy Creek Formation north of Lake Mead. Because no viable route for the ancestral Colorado River has been found anywhere in the Grand Canyon area, further surmised (by the process of elimination) that an interior closed lake basin may have existed in the Glen Canyon area from the middle to late Miocene (∼ 16-6 Ma) -possibly in continuation with Hunt's (1956) earlier lake.…”
Section: Hill Et Al Modelsupporting
confidence: 89%
“…4), this implies that a Miocene ancestral Colorado River never followed a westward route from the Glen Canyon area. This deduction agrees with the work of Pederson (2001), who found no evidence for an ancestral Colorado River having flowed west into the Muddy Creek Formation north of Lake Mead. Because no viable route for the ancestral Colorado River has been found anywhere in the Grand Canyon area, further surmised (by the process of elimination) that an interior closed lake basin may have existed in the Glen Canyon area from the middle to late Miocene (∼ 16-6 Ma) -possibly in continuation with Hunt's (1956) earlier lake.…”
Section: Hill Et Al Modelsupporting
confidence: 89%
“…Pederson (2008) studied the Muddy Creek north of Grand Canyon and concluded that these sediments did not represent terminal deposits from an ancestral Colorado River-the same conclusion as deduced by Hill et al (2008) based on Canaan Peaktype gravel distribution north of the canyon. In the southern Grand Wash fault area, near the mouth of Grand Canyon, the Muddy Creek Formation consists of three members that grade into and interfinger with each other:…”
Section: Headward Erosion From the Grand Wash Cliffsmentioning
confidence: 53%
“…During the Oligocene, the laccolithic Abajo and La Sal mountains formed and the uplift of these ranges and the Colorado Plateau as a whole, paired with the establishment of the modern Colorado River drainage (e.g., Pederson, 2008) and subsequent glacial-interglacial cycles during the Quaternary, was the primary driver of the erosional process that carved canyon country. The La Sals were glaciated repeatedly during the glacial-interglacial cycles of the Quaternary; the slightly older and lower-latitude Abajos were either not glaciated, or glaciers there were considerably smaller.…”
Section: Geology and Paleontologymentioning
confidence: 99%